BS EN 16272-3-1. Railway applications. Infrastructure. Noise barriers and related devices acting on airborne sound propagation. Test method for determining the acoustic performance. Part 3-1. Intrinsic characteristics. Normalized railway noise spectrum and single number ratings for diffuse sound field applications (17th February 2022) - British Standards Institution,
No abstract available